Association of preeclampsia with infant APOL1 genotype in African Americans - Anna K. Miller; Timur Azhibekov; John F. O'Toole; John R. Sedor; Scott M. Williams; Raymond W. Redline; Leslie A. Bruggeman (BMC, 2020)
Abstract Background Black women in the United States and Africa are at an increased risk for preeclampsia. Allelic variants in the gene for apolipoprotein LI, APOL1, are found only in populations of African ancestry, and have been shown to contribute significant risk for kidney disease. Recent studies suggest these APOL1 variants also may contribute risk for preeclampsia. Methods The association of preeclampsia with carriage of APOL1 risk alleles was evaluated in a case-control study of deliveries from black women at a single center in Cleveland, Ohio that included gross and histopathologic evaluations of placental tissues (395 cases and 282 controls). Using logistic regression models, associations between fetal APOL1 genotype and preeclampsia were evaluated using several case definitions based on prematurity and severity of preeclampsia, with uncomplicated term pregnancies as controls. Associations between APOL1 genotype and pathological features were also examined. Results The infant APOL1 genotype was significantly associated with preeclampsia in a dominant inheritance pattern with odds ratio of 1.41 (P=0.029, 95% CI 1.037, 1.926). Stratifying preeclampsia cases by preterm birth, significant associations were detected for both recessive (O.R.=1.70, P=0.038) and additive (O.R.=1.33, P=0.028) inheritance patterns. APOL1 genotype, however, was not significantly associated with pathological changes or other perinatal observations. Conclusions Preeclampsia appears to be another disease associated with APOL1 variants, however, further studies are needed to increase confidence in the mode of inheritance. By understanding the association of APOL1 variants with preeclampsia, genetic screening tests for APOL1 may be useful to predict at-risk pregnancies and targeted interventions may be developed to improve pregnancy outcomes.